2008
DOI: 10.1103/physrevlett.100.184101
|View full text |Cite
|
Sign up to set email alerts
|

Universality of Algebraic Decays in Hamiltonian Systems

Abstract: Hamiltonian systems with a mixed phase space typically exhibit an algebraic decay of correlations and of Poincaré recurrences, with numerical experiments over finite times showing system-dependent power-law exponents. We conjecture the existence of a universal asymptotic decay based on results for a Markov tree model with random scaling factors for the transition probabilities. Numerical simulations for different Hamiltonian systems support this conjecture and permit the determination of the universal exponent. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 18 publications
9
121
1
2
Order By: Relevance
“…(KAM) islands coexisting in a chaotic sea [21,25,42,43], and also in higher dimensions [49]. The power-law behavior is due to the nonhyperbolicity of the dynamics and it is present both for recurrences and escapes.…”
Section: Nonhyperbolic Hamiltonian Systems With Power-law Tailsmentioning
confidence: 99%
See 1 more Smart Citation
“…(KAM) islands coexisting in a chaotic sea [21,25,42,43], and also in higher dimensions [49]. The power-law behavior is due to the nonhyperbolicity of the dynamics and it is present both for recurrences and escapes.…”
Section: Nonhyperbolic Hamiltonian Systems With Power-law Tailsmentioning
confidence: 99%
“…[43] for the latest result that indicates that α ≈ 2.57). Here, for simplicity we write the asymptotic decay as n −α , but it is meant to describe the power-law like behavior usually observed.…”
Section: Nonhyperbolic Hamiltonian Systems With Power-law Tailsmentioning
confidence: 99%
“…The processes of types I and II are paradigms of various physical situations and the difference found here may give hope to develop statistical theories for mixed systems as proposed by [8][9][10] and others, and to classify relevant averaging processes into few classes. We start the calculation from (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recently an important contribution was made by Cristadoro and Ketzmerick who demonstrated the universality of the decay of correlations in the framework of the model of [8]. They examined an ensemble of such systems by using an arbitrary distribution of transition probabilities in phase space [9] . Guided by similar ideas, Ceder and Agam [10] used diagrammatic methods to calculate the exponent of the decay of correlations and its fluctuations and found that the fluctuations are large.…”
Section: Introductionmentioning
confidence: 99%
“…Several results observed in the literature also noticed this changeover. 28,31 A universality was proposed recently for the recurrence time 27 and power law decay was observed in different regions of the phase space for 2-D Hamiltonian systems [33][34][35][36] and for higher degrees of freedom Hamiltonian systems. 37 FIG .…”
Section: -7mentioning
confidence: 99%